KESENIAN SINGA LUGAY DI DESA SUKADANA KABUPATEN CIAMIS - Putri, Elfira Sofianni (2017)
Penelitianiniberjudul"KesenianSingaLugay Di DesaSukadanaKabupatenCiamis". Permasalahan yang diangkatpadapenelitianiniialahmengenaistrukturpenyajiandanunsur-unsurdalampenyajiankesenianSingaLugay. TujuandaripenelitianiniadalahuntukmendeskripsikandanmemberigambaransecaraumummengenaikesenianSingaLugay,Metode yang digunakandalampenelitianiniialahmetodedeskriptifanalisisdenganpendekatankualitiatif. Prosedurpenelitiandilakukandenganpengumpulan data, reduksi data, display data danpenarikankesimpulan. Teknikvalidasi data dilakukandengantriangulasi.Adapunhasildaripenelitianini , yakni keberadaan kesenian Singa Lugay merupakan hasil apresiasi Junaedi Wirasasmita terhadap kesenian Sisingaan,semenjak keberadaan kesenian Singa lugay hingga sekarang penyajian kesenian Singa lugay mengalami beberapa perubahan dilihat dari aspek pemain, gerak, atraksi, busana, danmusik. Dari beberapaaspektersebut yang paling menonjoladanyaperubahanpemainyang padaawalnyadimainkanolehlaki-lakimenjadidimainkanolehperempuanyang menyebabkanperubahanbusana,gerak, atraksi, danproperti. Kata Kunci :, Kesenian Sisingaan, Kelompok Singa Lugay, Ciamis, Art SingaLugay at Sukadana Village Ciamis Region is a title in this research. The issues raised in this researchis about structure of presentation and elements in the presentment of art SingaLugay. The Purpose of this research is to describe and provide an overview in general about Art SingaLugay. The method used is descriptive analysis through a qualitative approach, research procedur done with data collect, data reduction, display and conclusion. Data validation done with triangulation. As for result, existence of art SingaLugay is the result of JunaediWirasasmita Appreciation of art Sisingaan from Subang. Since the existence art SingaLugay until now , presentment of art SingaLugayhas undergone some changes seen from aspect players, movement, attraction, property, costume and music, of these the most prominent aspect is player changes which the beginning was play by men now being played by women who cause change in costume, movement, attraction and properties Keyword: ArtSisingaan, SingaLugay, Ciamis